2021
DOI: 10.1002/pc.26025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon fiber type and resin ratio on thermal and mechanical lifetime of polyetherimide composites

Abstract: The aim of this study is to develop and characterize carbon fiber (CF)‐reinforced polyetherimide (PEI) composite materials that can be used in aerospace and defense industries. Four different composite materials with 60/40 and 40/60 resin/fiber weight ratios were prepared by hand lay‐up using unidirectional (UD) CFs and TWILL CFs. It was determined that, the thermal stability of composite materials is independent of CFs. PEI resin and composite materials soften above 200°C and decompose above 500°C. Also, PEI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The ratio of the PAN in the resin solution prepared and the weight of the carbon fibers must be in an equal ratio to ensure a good composite with greater bond strength. 9,10 The amount of PAN utilized for this process was 50 g. Therefore, carbon fibers weighing 50 g (with seven layers of carbon fibers) were utilized for the wet layup of the composite process. Figure 3 shows the process flow of the PAN based fiber reinforced C-C composite manufacturing.
Figure 3.Process flow diagram of the PAN based fiber reinforced C-C composite manufacturing.
…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of the PAN in the resin solution prepared and the weight of the carbon fibers must be in an equal ratio to ensure a good composite with greater bond strength. 9,10 The amount of PAN utilized for this process was 50 g. Therefore, carbon fibers weighing 50 g (with seven layers of carbon fibers) were utilized for the wet layup of the composite process. Figure 3 shows the process flow of the PAN based fiber reinforced C-C composite manufacturing.
Figure 3.Process flow diagram of the PAN based fiber reinforced C-C composite manufacturing.
…”
Section: Methodsmentioning
confidence: 99%
“…The main preparation processes for short carbon fiber reinforced thermoplastic composites are wet preparation process and mixing preparation process, which will all reduce the fiber length 14,15 . Wet molding process is mainly spiral stirring dispersion of carbon fibers, fiber length is significantly shorter, not conducive to the preparation of high‐performance composites 16 . Currently, the length of fibers used for the preparation of short carbon fiber composites range between (3–10 mm), When fiber length is between (3–10 mm), CFRTP mainly rely on the resin bonding, and increasing the fiber length can improve the fiber embedded in the resin length, improve the mutual hook between the fibers and the mechanical properties of CFRTP.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic composites have excellent toughness, secondary processability and recyclability, and have attracted more and more attention in recent years 1–4 . Among them, continuous carbon fiber reinforced polyether ether ketone (PEEK) composites are widely used in aviation, marine, and automotive industries because of their excellent performance –6 .…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic composites have excellent toughness, secondary processability and recyclability, and have attracted more and more attention in recent years. [1][2][3][4] Among them, continuous carbon fiber reinforced polyether ether ketone (PEEK) composites are widely used in aviation, marine, and automotive industries because of their excellent performance. -6 Studies on the interfacial properties of carbon fiber reinforced PEEK composites showed that the fiber-resin interface is significantly higher compared to that of other thermoplastic systems.…”
Section: Introductionmentioning
confidence: 99%